The effects of stress on workers of emergency team and job satisfaction - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta; Klimaszewska, Krystyna; Kondzior, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Specific character of medical rescuer work requires agreement between members of emergency. Quality and efficacy of rescue functions requires establishment of the appropriate organizational structure in the emergency. Aim of the study. to present the influence of patients and coworkers aggressive behaviour on work satisfaction amongst the population of medical rescue workers; to determine the influence of integrated health care team tension on the attitude towards the work performed. Material and methods. Studies were carried out at the turn of April and May 2008 among 126 medical rescue workers working in the hospital treatment within Podlaskie Voivodeship. Questionnaires assessing the sort of aggression towards medical rescue workers and General Health Questionnaires were used. Research material collected was verified statistically by means of chi-square test. Results. Almost 43% of responders whose did not like their job were subjected to chief aggression (threats and blackmails). Responders whose liked their job were subjected to aggression (9% to threats and 6% to blackmails). All responders (100%) whose specified atmosphere in the workplace as "unpleasant" had experienced aggression from patients, they "dangerous" and "vulgar" in the presence of co-workers. In the study group 69% of responders specified atmosphere as pleasant in the workplace. They were subjected to aggression from patients "dangerous" and 76% "vulgar behaviors in front of patients". Conclusions. Percentage of medical rescuers whose experienced chief and co-workers aggression was higher whose did not like their job compared to those liked their job. specified Aggressive behaviors of patients did not effect on attitude to job.